An analysis of the historical and cultural process of construction of scientific knowledge - Danillo Deus Castilho; Weimar Silva Castilho (Universidade Federal do Oeste da Bahia, 2020)
The following is a theoretical study on the development of scientific knowledge. This effort is necessary to deepen the understanding of scientific practice, avoiding, for example, using in science teaching only lessons based on the hypothetical-deductive method, and, therefore, being careful when bringing science together with teaching/learning science. Through one of the references of historical-cultural theory, we will analyze the process of elaboration of this knowledge. In this sense, we present an alternative to apprehend the possible logical-structural modes of Galileo Galilei's thought. Thus, we turn our attention to his reports on the discovery of Jupiter's moons, in January 1610, in search of the possible reasons that led Galileo to deepen his knowledge of the natural world.